An Anti-Inflammatory Composition of Boswellia serrata Resin Extracts Alleviates Pain and Protects Cartilage in Monoiodoacetate-Induced Osteoarthritis in Rats. (22nd May 2020) - Alluri, Venkata Krishnaraju; Kundimi, Sreenath; Sengupta, Krishanu; Golakoti, Trimurtulu; Kilari, Eswar Kumar
Abstract : The boswellic acids, the active compounds in Boswellia serrata gum resin extract, are potent anti-inflammatory agents and are specific nonredox inhibitors of 5-Lipoxygenase (5-LOX). Here, we present the anti-osteoarthritis (OA) efficacy of LI13019F1 (also known as Serratrin®), a unique composition containing the acidic and nonacidic fractions of B. serrata gum resin. This composition strongly inhibited 5-LOX activity with the half-maximal inhibitory concentration (IC50 ) of 43.35 ± 4.90 μ g/mL. Also, LI13019F1 strongly inhibited the leukotriene B4 (IC50, 7.80 ± 2.40 μ g/mL) and prostaglandin E2 (IC50, 6.19 ± 0.52 μ g/mL) productions in human blood-derived cells. Besides, LI13019F1 reduced TNF- α production with the IC50 of 12.38 ± 0.423 μ g/mL. On average, 1, 2.5, and 5 μ g/mL doses of LI13019F1 protected 34.62, 47.66, and 62.29% SW1353 human chondrosarcoma cells from IL-1 β induced SOX-9 depletion, respectively. Further, a 28-day preclinical proof-of-concept study evaluated the pain relief efficacy of LI13019F1 in monoiodoacetate- (MIA-) induced Sprague-Dawley rats. At the end of the study, 150 and 300 mg/kg doses of LI13019F1 supplemented rats showed significant improvements (55.17 ± 5.81 g (p < 0.05 ), and 66.22 ± 6.30 g (p < 0.05 ), respectively, vs. MIA: 31.22 ± 7.15 g) in body-weight-bearing capacities. Concurrently, LI13019F1-150 and LI13019F1-300 rats substantially (p < 0.05 ) increased the threshold of pain sensitivity to pressure (26.98 ± 2.36 and 28.06 ± 2.72-gram force, respectively; vs. 18.63 ± 5.82 in MIA) and increased (p < 0.05 ) the latent time to withdraw the paw after a thermal stimulus (23.61 ± 2.73 and 28.18 ± 1.90 sec, respectively; vs. 16.56 ± 1.22 sec. in MIA). Besides, the histological observations on Safranin-O green stained articular cartilage revealed that LI13019F1 also prevented the MIA-induced structural damage of the cartilage and reduced the loss of the extracellular matrix (ECM) components in the experimental rats. In conclusion, the present observations suggest that LI13019F1, a new composition of B. serrata gum resin extracts, reduces pain and protects articular cartilage from the damaging action of MIA in a rodent model.